Nonparametric statistics for social and behavioral sciences - Kraska-Miller, M. (Marie) (Taylor and Francis, an imprint of Chapman and Hall/CRC, 2013)
Incorporating a hands-on pedagogical approach, Nonparametric Statistics for Social and Behavioral Sciences presents the concepts, principles, and methods used in performing many nonparametric procedures. It also demonstrates practical applications of the most common nonparametric procedures using IBM's SPSS software.